Kedudukan Informed Consent Pada Pelayanan Pasien Di Rumah Sakit - Redyanto Sidi (Iuris Studia: Jurnal Kajian Hukum, 2020)
In this informed consent, many patients do not know the extent of their rights as recipients of health services, and hospitals and doctors as health service providers are obliged to carry out their obligations for the benefit of patients. As a patient should also accept the advice given by the doctor. The relationship between doctor and patient arises when the patient first comes with the intention of seeking help. From that moment on, what is meant by Informed consent, namely the arrival of a patient, which means he has given confidence to the doctor, automatically implants an attitude that aims to prioritize the health of his patient. This research is a normative legal research that refers to the legal rules in the order of legislation and principles in applicable law in Indonesia regarding the regulation of the legal aspects of the doctor's therapeutic agreement in providing medical treatment to patients in hospitals. Informed consent, also known as consent for medical action, is a relationship that occurs between a doctor and a patient in a hospital, which is basically a form of agreement, which can be viewed from a deceptive legal point of view, where the patient must understand and have sufficient information to make decisions regarding care for himself and consent for the treatment to be given by the patient both in writing and orally. Because informed consent is the agreement or permission by the patient or family who has the right to the doctor to take a medical action on him and get a complete explanation is one of the rights of the patient in the hospital